Optimal load for managing low-risk tibial and metatarsal bone stress injuries in runners: The science behind the clinical reasoning - Warden, S. J.; Edwards, W. B.; Willy, R. W. (Journal of Orthopaedic & Sports Physical Therapy, 2021)
Background: Low-risk bone stress injuries (BSIs) of the tibia and metatarsal diaphyses account for more than half of BSIs in runners. They interrupt training and are managed using noninvasive approaches that are designed to achieve a speedy but safe return to running. Clinical Question: What is the optimal load to manage low-risk tibial and metatarsal BSIs and safely return to running? Key Results: Optimal load can be guided by knowledge of the BSI healing process and is symptom driven. At all stages, the optimal load does not produce symptoms during, after, or the day following loading. Clinical Application: A period of initial load reduction, via partial or non-weight bearing, is typically needed to alleviate presenting symptoms. Analgesics or nonsteroidal anti-inflammatory drugs may be used in the short term (sooner than 7 days), but only for resting pain and night pain. Healing supplements (eg, low-intensity pulsed ultrasound and/or recombinant parathyroid hormone therapy) may be attempted to influence tissue healing. Athletes can maintain cardiopulmonary fitness via cross-training, while simultaneously addressing musculoskeletal fitness. A return-to-run program can be initiated once an athlete is pain free during daily activities for 5 consecutive days. Progress is directed by symptom provocation and initially focuses on increasing running volume before speed. Optimal loading should be continued following return to running and may include jump training and/or gait retraining to reduce subsequent BSI risk. The optimal loading approach to managing low-risk tibial and metatarsal BSIs is clinically successful, but requires further scientific validation.